Impact of E-Learning Module in Learning English Language Skills during Covid - 19 Pandemic: An Experimental Study (International Journal of Food and Nutritional Sciences, 2022)
This study was conducted to investigate the impact of e-learning module in learning English language skills - listening, speaking, reading, writing. 50 secondary student teachers were selected by the investigator as the sample of the study. The investigator has adopted the experimental method with Pre-test Post-test Equivalent Group Design. E-learning module to teach the four skills – Listening, Speaking, Reading and Writing in English was developed by the investigator and then analysis of data was done using mean and „t‟-test. The result of the study reveals that there is significant difference between the scores obtained by the control group in pre-test and post-test.Also there is significant difference between the scores obtained by the experimental group in pre-test and post-test. And also effect sizeanalysis was carried out to find the effectiveness of e-learning module over the conventional teaching method. Cohen‟s d for effect size for the control group and experimental group to the mean scores for pretest is Cohen‟s d=0.02488, r=0.003 and for posttest Cohen‟s d=0.7073, r= 0.3. Hence it is concluded that the large effect size is due to the implementation of e-learning module to the experimental group.